Association of Health Status With Receipt of Supplemental Security Income Among Individuals With Severe Disabilities and Very Low Income and Assets - Sonik, Rajan A. (JAMA Intern Med, 2019)
This study assesses the association of health status with receipt of Supplemental Security Income by comparing the health patterns among individuals before vs after entry into the program.